Effects of vermicomposting duration to macronutrient elements and heavy metals concentrations in Vermicompost - Jamaludin, A.A.; Mahmood, N.Z. (Penerbit Universiti Kebangsaan Malaysia, 2010)
Vermicomposting using Lumbricus rubellus was conducted in two different durations, 10 and 30 weeks in the same plots. Three different of treatments combination were prepared with eight replicates for each treatment namely cow dung : kitchen waste in 30:70 ratio (T1), cow dung : coffee grounds in 30:70 ratio (T2), and cow dung : kitchen waste : coffee grounds in 30:35:35 ratio (T3). Macronutrients elements in the vermicompost from each treatment were measured in the tenth and thirtieth week. Comparatively longer duration of vermicomposting by using Lumbricus rubellus enhanced the quality of vermicompost by the increase of the macronutrient elements while reducing the heavy metal concentration and CIN ratio.